Stepping-Up Technology Implementation—How Does it Happen?. Issue 1 (March 2023) - Evmenova, Anya S.; Regan, Kelley S.; Schladant, Michelle; Hall, Tracey E.; Buzhardt, Jay; Erickson, Karen A.; Ai, Jun; Sudduth, Christina; Jackson, Terry
While technology-based interventions enhance instruction and improve outcomes for students with disabilities, implementing and integrating technology in authentic learning environments continues to be a challenge. Based on the experiences of a variety of Stepping-Up Technology Implementation projects funded by the U.S. Department of Education, Office of Special Education Programs, this mixed-methods study explored the essential factors for the successful implementation of technology-based interventions in K-12 schools and early childhood programs. Based on the qualitative analysis of projects' implementation reports and responses to the follow-up questionnaire, four major themes emerged. The barriers and facilitators to technology implementation were reported across such areas as (a) developing and sustaining buy-in, (b) ensuring implementation fidelity to support the intervention, (c) research-to-practice dilemmas, and (d) data serving multiple purposes. The discussion and practical implications for supporting technology implementation are provided.